Disruption of fos causes craniofacial anomalies in developing zebrafish - Maili, Lorena; Tandon, Bhavna; Yuan, Qiuping; Menezes, Simone; Chiu, Frankie; Hashmi, S. Shahrukh; Letra, Ariadne; Eisenhoffer, George T.; Hecht, Jacqueline T. (Frontiers in Cell and Developmental Biology, 2023)
Craniofacial development is a complex and tightly regulated process and disruptions can lead to structural birth defects, the most common being nonsyndromic cleft lip and palate (NSCLP). Previously, we identified FOS as a candidate regulator of NSCLP through family-based association studies, yet its specific contributions to oral and palatal formation are poorly understood. This study investigated the role of fos during zebrafish craniofacial development through genetic disruption and knockdown approaches. Fos was expressed in the periderm, olfactory epithelium and other cell populations in the head. Genetic perturbation of fos produced an abnormal craniofacial phenotype with a hypoplastic oral cavity that showed significant changes in midface dimensions by quantitative facial morphometric analysis. Loss and knockdown of fos caused increased cell apoptosis in the head, followed by a significant reduction in cranial neural crest cells (CNCCs) populating the upper and lower jaws. These changes resulted in abnormalities of cartilage, bone and pharyngeal teeth formation. Periderm cells surrounding the oral cavity showed altered morphology and a subset of cells in the upper and lower lip showed disrupted Wnt/β-catenin activation, consistent with modified inductive interactions between mesenchymal and epithelial cells. Taken together, these findings demonstrate that perturbation of fos has detrimental effects on oral epithelial and CNCC-derived tissues suggesting that it plays a critical role in zebrafish craniofacial development and a potential role in NSCLP.